IDENTIFICATION OF ORNAMENT AND FAUNA POTENTIAL OF SIBIUK CAVE IN CIAMPEA BOGOR SUBDISTRICT - Ratna Sari Hasibuan; Ken Dara Cita; Fathul Ilmi (Media Konservasi, 2020)
The beauty of ornament and uniqueness of cave is the potential of Sibiuk Cave that could be made into special interest tourism. Sibiuk Cave is known as Air Conditioner Cave for it has three doors that make the cave cold inside. This study aims to identify the potential that Sibiuk Cave has, which located in Ciampea Subdistrict. This study was conducted from February to May 2020 by applying survey forward method and top to bottom survey system in making Sibiuk Cave profile map and direct collection with rapid assessment method to identify cave ornament and fauna. The results of the study were the existence of stalactites, stalagmite, chamber, column, and boulder as well as faunas such as ancient shrimp (Stenasellus sp), cave cricket (Rhaphidophora sp), tailless whip scorpion (Stygophrynus dammermani), whip scorpion (Thelyphonus caudatus), millipede (Orthomorpha coarctata), land snail (Leptopoma celebesianum), centipede (Scutigeria sp), bat (Rousettus amplexicaudatus), and swift (Collocalia vestita). SIbiuk cave potential is expected to be expanded into special interest tourism of rock climbing, caving, speleology and biospeleology. Key words: cave fauna, sibiuk cave, cave ornament, forward survey